2019
DOI: 10.5194/gmd-2019-248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing model errors in chemical transport modeling of methane: Impact of model resolution in versions v9-02 of GEOS-Chem and v35j of its adjoint model

Abstract: Abstract. The GEOS-Chem simulation of atmospheric CH4 was evaluated against observations from the Thermal And Near infrared Sensor for carbon Observations Fourier Transform Spectrometer (TANSO-FTS) on the Greenhouse gases Observing SATellite (GOSAT), the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS), and the Total Carbon Column Observing Network (TCCON). We focused on the model simulations at the 4° × 5° and 2° × 2.5° horizontal resolutions for the period of February–May 2010. Compa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…The spatial resolution is varied to examine whether changes in model transport significantly impact our results. It has previously been shown that there are significant differences in tracer transport as model resolution is decreased in GEOS-Chem (Yu et al, 2018;Stanevich, 2018). In particular, Stanevich (2018) show that resolution-induced biases of up to 30 % can be introduced on the scale of TransCom regions for 4 • × 5 • relative to 2 • × 2.5 • for atmospheric methane (CH 4 ) inversions.…”
Section: Geos-chemmentioning
confidence: 91%
See 1 more Smart Citation
“…The spatial resolution is varied to examine whether changes in model transport significantly impact our results. It has previously been shown that there are significant differences in tracer transport as model resolution is decreased in GEOS-Chem (Yu et al, 2018;Stanevich, 2018). In particular, Stanevich (2018) show that resolution-induced biases of up to 30 % can be introduced on the scale of TransCom regions for 4 • × 5 • relative to 2 • × 2.5 • for atmospheric methane (CH 4 ) inversions.…”
Section: Geos-chemmentioning
confidence: 91%
“…The results of this study indicate that the spatial resolution of the model used in the inversion analysis (2 • × 2.5 • or 4 • × 5 • ) has a relatively minor impact on posterior NEE anomalies. This somewhat surprising since recent studies (Yu et al, 2018;Stanevich, 2018) have shown significant transport differences for different resolution versions of GEOS-Chem. Also, Deng et al (2015) showed that there are large biases in CO 2 in the upper troposphere and lower stratosphere in GEOS-Chem that impact inferred flux estimates.…”
Section: Model Horizontal Resolutionmentioning
confidence: 94%
“…This is thought to result from excessive meridional transport in the stratosphere, a common problem in global models (Patra et al, 2011). In particular, coarse-resolution global models have difficulty resolving polar vortex dynamics that control the distribution of stratospheric methane in the winter-spring hemisphere (Stanevich et al, 2019). GEOS-Chem model evaluation with stratospheric sub-columns derived from ground-based TCCON column measurements shows that the stratospheric bias varies seasonally (Saad et al, 2016).…”
Section: Forward Model Bias Correctionmentioning
confidence: 99%
“…has a relatively minor impact on posterior NEE anomalies. This somewhat surprising since recent studies (Yu et al, 2018;Stanevich, 2018) have shown significant transport differences for different resolution versions of GEOS-Chem. Also, Deng et al (2015) showed that there are large biases in CO 2 in the upper troposphere and lower stratosphere in GEOS-Chem that impact inferred flux estimates.…”
Section: Model Horizontal Resolutionmentioning
confidence: 92%
“…The spatial resolution is varied to examine whether changes in model transport significantly impact our results. It has previously been shown that there are significant differences in tracer transport as model resolution is decreased in GEOS-Chem (Yu et al, 2018;Stanevich, 2018). In particular, Stanevich (2018) show that resolution-induced biases of up to 30% can be introduced on the scale of TransCom regions for 4°× 5°relative to 2°× 2.5°for atmospheric methane (CH 4 ) inversions.…”
Section: Nino 34 Indexmentioning
confidence: 94%